Frontline Ph-negative B-cell precursor acute lymphoblastic leukemia treatment and the emerging role of blinatumomab - Elias J. Jabbour; Hagop M. Kantarjian; Nicola Goekbuget; Bijal D. Shah; Sabina Chiaretti; Jae H. Park; Anita W. Rijneveld; Lia Gore; Shaun Fleming; Aaron C. Logan; Josep M. Ribera; Tobias F. Menne; et al. (Blood Cancer Journal)
Abstract This narrative review seeks to summarize chemotherapeutic regimens commonly used for patients with newly diagnosed Philadelphia (Ph) chromosome–negative B-cell precursor acute lymphoblastic leukemia (BCP-ALL) in the frontline setting and to describe the latest clinical research using the bispecific T-cell–engaging immunotherapy blinatumomab in the first-line treatment setting. Current standard-of-care chemotherapeutic backbones for newly diagnosed Ph-negative BCP-ALL are based on the same overarching treatment principle: to reduce disease burden to undetectable levels and maintain lasting remission. The adult treatment landscape has progressively evolved following the adoption of pediatric-inspired regimens. However, these intense regimens are not tolerated by all, and high-risk patients still have inferior outcomes. Therefore, designing more effective and less toxic strategies remains key to further improving efficacy and safety outcomes. Overall, the treatment landscape is evolving in the frontline, and integration of blinatumomab into different standard frontline regimens may improve overall outcomes with a favorable safety profile.